An exploration into change management perceptions and approaches of two provincial government departments - Ndlovu, Zibusiso Khethiwe (University of the Witwatersrand, Johannesburg, 2023)
Change in the South African public sector is unavoidable due to the turbulent political and economic climate and developing technologies presented to us by the 4th industrial revolution. It is widely acknowledged that organizational change is often plagued by failure, however, this study argues that contextual organisational dimensions such as deep structures and change ownership are frequently overlooked in public sector change management discussions. This prompted a qualitative case study between two Gauteng Provincial Government departments. This design enabled an in-depth exploration of approaches to change management in the two different departments to gain a better understanding of change management approaches within the GPG. Data was collected from recorded 30–60-minute semi-structured interviews with 12 key informants (senior, middle, and junior management staff in the respective provincial departments) identified through purposive criterion & snowball sampling. Interviews were transcribed identifying emerging themes and codes aligned to answering the research questions. Additionally, a desktop review of academic literature, departmental documents, and reports was undertaken to gain deeper contextual understanding and perspective of the GPG change management landscape. The study results revealed that the nature of change is characterised by a lack of ownership and poor reinforcement of change in the GPG. Furthermore, that communication within GPG exists, however, it doesn’t always filter down to the lowest employees
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management Governance (Public and Development Sector Monitoring and Evaluation) to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2023
Keywords: Change Management; Provincial Government; Perceptions; Approaches; Management; UCTD; SDG-11: Sustainable cities and communities